Religious involvement and sociodemographic factors: a Brazilian national survey (Archives of Clinical Psychiatry, 2010)
BACKGROUND: The relationship between religious involvement and health has been subject to an increasing interest. However, studies investigating religious involvement are scarce outside United States and Europe. OBJECTIVES: This study describes religious involvement in the Brazilian population and its relationship with sociodemographic variables. METHODS: In a Brazilian nationally probabilistic sample (n = 3,007), religious involvement variables and sociodemographic factors were assessed. RESULTS: Five percent of Brazilians reported having no religion, 83% considered religion very important in their lives, and 37% attended religious services at least once a week. The most frequent affiliations were Catholicism (68%), Protestant/Evangelicals (23%), and Kardecist Spiritism (2.5%). Ten percent reported attending more than one religion. In line with studies in other countries, older age and female gender were independently associated with higher levels of subjective and organizational religiousness after controlling for other sociodemographic factors. However, educational level, income and black race were not independently associated with religious involvement variables. DISCUSSION: This study shows high levels of religious involvement among Brazilians and suggests that religiousness may have different associations with other variables across different cultures. To better understand the influence of religion on health, it is necessary to expand this kind of survey to other cultures.